Message From The Editor - Editor, Chief (Journal of Technical Education and Training, 2015)
Welcome to the December 2015 issue of JTET.  In this issue we share with our readers six articles from our international contributors who have generously shared their critical reviews and research findings on the various aspects of TVET from research concerns to training to employability of TVET graduates. The first article by Mohd Affandi, Amiruddin, Che Hassan, and Zainudin, describes the current status of academics with regards to the factors that may predispose them to participate in research. It arises out of concern by management on the low participations of TVET academics in research undertakings.  The second article by Irdayanti, Ramlee, and Abdullah discusses a useful research technique - but nevertheless less widely used by TVET researchers - the Delphi technique.  It is expected that readers can benefit from this paper irrespective of their research paradigms; quantitative or qualitative. Moving from research to skills acquisitions; basic technological skills and higher order thinking skills are the basis for acquisition of advanced technological skills in particular as well as advancement in the general TVET sector. Thus, having students do well in both areas is of much interest to TVET educators.  Status of Nigerian students on their basic technological skills are discussed in the third paper by Igberadja while effective strategies for  developing higher order thinking skills among TVET students are discussed in the fourth paper by  Chinedu, Kamin and Olabiyi. Technological skills and higher order thinking skills are however, not the only skills to be acquired by TVET graduates; people skills are also equally important.  People skills related to employment are best developed through working in industries which provide opportunities for developing these skills in authentic environments that will enhance employability of TVET graduates.  Thus, industrial training - be it in the final year or mid programme - is seen as an important component of TVET curriculum irrespective of level of studies. When implemented in the final semester of a programme of study, its impact on employability is naturally is the primary interest to educators. However, when industrial training is implemented in mid-programme, its impact on course outcomes becomes the primary interest to educators. To provide an idea on its impact on course outcomes, the fifth paper, by Megat Mohd Nor and Ismail, reports on the impact of industrial training on students academic achievement.   In addition to industrial trainings, efforts to enhance engineering graduate employability and self-sufficiency have recently focused on entrepreneurship skills training. Being at its infancy stage of implementation in Malaysia; factors that influent success of such programmes has yet to be fully understood.  Gender difference on certain aspects of entrepreneurial pursuits for example has been indicated to be a contributing factor to success in entrepreneurship training. In the last paper, Abbas discusses the interacting roles of entrepreneurial intention and gender for a better understanding of success factors in entrepreneurship programme. I hope these articles are of interest to our readers. Last but not least, thank you to all our authors for making this issue possible. To our reviewers, thank you for helping us in ensuring JTET achieve the high quality that it is aiming for. We hope everyone; from authors to reviewers will continue to give their strong support so that we can continue to provide the knowledge sharing that is made possible through research publications by global TVET practitioners and researchers.   Prof. Dr. Maizam Alias